Experimental Study of the Chimney Height Variation Against Double Pots Biomass Stove Performance - Faisal, Faisal; Setiawan, Adi; Wusnah, Wusnah; Khairil, Khairil; Luthfi, Luthfi; Fajriana, Mona (UI Scholars Hub, 2017)
This research aims to get optimal chimneys height of double pots biomass stove. Optimal chimneys height needs to provide best performance of the stove. Experimental study was done by varied the chimney heights. Water boiling test as the standard method was used to obtained stove performance for each chimney height variation. The results showed that best performance stove was the one with 1.65 cm chimney height, with thermal efficiency at 37.66%.